Implementasi Metode Profetik Pada Pelajaran Tematik Di Kelas II SDN Kadu 2 Bitung - Wahyu Ningsih; Anggun Sri Rahayu; Nur Fadiyah (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2024)
The awareness of teachers in general studies education who teach general "thematic" lessons is only to convey knowledge, without also conveying how to increase and apply faith and also protect students from teaching materials that can damage students' selves. This research focuses on how to apply the prophetic method at SDN Kadu 2 using descriptive qualitative research methods. Meanwhile, the method used to collect data is through observation and interviews with related parties. To analyze the data, researchers used qualitative descriptive analysis techniques, namely describing the data that has been collected to describe reality according to actual phenomena. In conducting interviews, the researcher determined the research subject to the teacher who taught thematic lessons, in this case, of course, the Class II teacher was very concerned. The result of this research is that the implementation of the prophetic method at SDN Kadu 2 has been implemented by teachers. The teacher has applied the prophetic method as a method for delivering lessons by adapting to conditions in the field. The conclusion is that using the prophetic method by adjusting the lesson theme can be a solution, so that students avoid damaged understanding. All of this can be easily done when the teacher has strong religious knowledge and a correct Islamic worldview.